Urethanes and polyurethanes from suberin 2: synthesis and characterization (INDUSTRIAL CROPS AND PRODUCTS, 1999)
Polyurethanes based on suberin from cork of Quercus suber L. and conventional isocyanate monomers were prepared and fully characterized in terms of both structure (FTIR and H-1 NMR spectroscopy) and thermal properties (differential scanning calorimetry and thermogravimetric analysis). Two fractions were systematically isolated, namely (i) methylene-chloride soluble products, which corresponded to linear and branched macromolecules and (ii) methylene-chloride insoluble products, representing the crosslinked material. The structures of these polymers were regular and no appreciable side reactions were detected. DSC analyses provided information about the glass transition temperature of both fractions and this parameter was correlated with the stiffness of the isocyanate used. The TGA of these polyurethanes showed that they started to degrade at about 175 degrees C and that the residue at 400 degrees C was around 50%. The highest amounts of insoluble fractions, as well as the highest T-g,s, were reached when an initial \{[\}NCO]/\{[\}OH] of unity was used. (C) 1999 Elsevier Science B.V. All rights reserved.